Implantação da metodologia BIM na gestão da manutenção da unidade de Oncohematologia pediátrica do Hospital das Clínicas da UFMG - Hugo Sávio Penna Aleixo (2023)
Facility Management involves the management of people, processes, and spaces. When integrated into the Building Information Modeling (BIM) methodology, it enables effective management of information flow. The management of spaces, assets, and maintenance through BIM-FM has shown promise, aiming to reduce decision-making time and enhance result accuracy. In this context, the present study aims to apply the BIM methodology to the development of maintenance management for the Pediatric Oncohematology unit of the Hospital das Clínicas at the Federal University of Minas Gerais, involving space and assets. The proposed tool for discipline modeling is the Revit platform, and for facility management development, the Archibus system is utilized. The study describes the current Facility Management process of the mentioned hospital facility, identifying possibilities for improvements, challenges, and difficulties in adopting the new BIM construct. To achieve this, the research methodology follows the principles of Constructive Research, contributing scientifically by offering an innovative approach in BIM-FM application. This approach accomplishes the following: a) Regarding spaces and assets, it centralizes and identifies information with precision, leading to more accurate decision-making b) Regarding maintenance, it expedites access to information to facilitate changes and interventions in the studied environment's facilities.